STRATEGI PARTAI DEMOKRAT DALAM MENGUSUNG DAN MENENTUKAN BAKAL CALON BUPATI DAN BAKAL CALON WAKIL BUPATI NIAS SELATAN PERIODE 2020-2025 - Madin Silalahi; Dermanjaya Laia (JURNAL GOVERNANCE OPINION, 2021)
The purpose of mapping the right strategy is to achieve the goals and objectives as expected and can also have a positive impact on the entire community through political education and increase public participation in democracy. The research method used is to find concrete answers in the field and to determine informants in order to obtain accurate information and data through interviews, documentation, research techniques and observation (observations). The research method is a qualitative approach with 15 informants. The conclusion is that the strategy carried out by the Democratic Party must go through a regulatory mechanism and be in line with the vision and mission of the Democratic Party. In addition, inhibiting factors, both internally and externally, also become obstacles in the process of determining the candidate pairs to be carried later in the Election of the Head of the Regional Head of South Nias in December 2020, they must also be coordinated with the DPD (Regional Representative Board) of the Democratic Party of North Sumatra. The community's response and the forms of participation provided by the community in the Election of the Head of the South Nias Region must choose a candidate pair who has a track record that is known by the community before giving their political choice and can run well and conducive.